2020
DOI: 10.1002/anie.202001508
|View full text |Cite
|
Sign up to set email alerts
|

Titanocenes as Photoredox Catalysts Using Green‐Light Irradiation

Abstract: Irradiation of Cp2TiCl2 with green light leads to electronically excited [Cp2TiCl2]*. This complex constitutes an efficient photoredox catalyst for the reduction of epoxides and for 5‐exo cyclizations of suitably unsaturated epoxides. To the best of our knowledge, our system is the first example of a molecular titanium photoredox catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 81 publications
1
44
0
2
Order By: Relevance
“…[75] The groups of Gansäuer and Flowers lately reported the use of Cp 2 Ti IV Cl 2 as the sole photoactive species in the reductive opening of aliphatic epoxides (Scheme 11). [76] Relying on the analysis of the bimolecular quenching, the authors showed that Scheme 11. Titanocene as photocatalyst in the reductive ring opening of epoxides.…”
Section: Titanocenes In Metallaphotoredox Catalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[75] The groups of Gansäuer and Flowers lately reported the use of Cp 2 Ti IV Cl 2 as the sole photoactive species in the reductive opening of aliphatic epoxides (Scheme 11). [76] Relying on the analysis of the bimolecular quenching, the authors showed that Scheme 11. Titanocene as photocatalyst in the reductive ring opening of epoxides.…”
Section: Titanocenes In Metallaphotoredox Catalytic Reactionsmentioning
confidence: 99%
“…The groups of Gansäuer and Flowers lately reported the use of Cp 2 Ti IV Cl 2 as the sole photoactive species in the reductive opening of aliphatic epoxides (Scheme 11). [ 76 ] Relying on the analysis of the bimolecular quenching, the authors showed that the excited triplet state of Cp 2 Ti IV Cl 2 ( E 00,T ≈ 2.14 eV; E * red,T ≈ 1.39 V vs. SCE), produced upon excitation of its low‐energy lying LMCT transition, is effectively quenched in the presence of N,N ‐diisopropylethylamine (DIPEA), leading to the corresponding transient ion pair which eventually evolves in the Ti III redox‐active species. The carbon center radical formed performs a hydrogen atom transfer (HAT) process with methyl thioglycolate to give the corresponding Ti IV ‐alkoxy species.…”
Section: Titanocenes In Metallaphotoredox Catalytic Reactionsmentioning
confidence: 99%
“…Further, the first example of a molecular Ti photoredox catalyst was only reported very recently. [30] In this publication, a titanocene complex was irradiated with green LEDs (530 nm) and used to promote the reduction and cyclisation of epoxides. Although not strictly a PS, this photoredox catalyst is included at this point, in order to display the scarcity of reports of photoactive Ti complexes and highlight the opportunities for future research, which may arise from these two innovative examples.…”
Section: Titanium Photosensitisersmentioning
confidence: 99%
“…Further, the first example of a molecular Ti photoredox catalyst was only reported very recently [30] . In this publication, a titanocene complex was irradiated with green LEDs (530 nm) and used to promote the reduction and cyclisation of epoxides.…”
Section: Examples Of First‐row Transition‐metal Photosensitisersmentioning
confidence: 99%
“…Recently, the Gansäuer group reported that Cp 2 TiCl 2 itself can act as a photoredox catalyst under greenlight irradiation (Scheme 1, c). [27] In the presence of a reductive quencher, such as N,N-diisopropyl ethyl amine (DIPEA), shortlife photoexcited Cp 2 TiCl 2 could be directly reduced to Cp 2 Ti III Cl without the aid of additional photocatalysts. The bimolecular quenching constant for photoexcited Cp 2 TiCl 2 and DIPEA was determined to be 1 × 10 4 L .…”
Section: Introductionmentioning
confidence: 99%